The political use of the cult of St. Tryphon of Pechenga and its potential as a bridgebuilder in the Arctic - Kahla, Elina (2023)
The book argues that religion is a system of significant meanings that have an impact on other systems and spheres of social life, including cultural memory. Elina Kahla's case studyon the cult of of St. Tryphon of Pechenga shows that, for each of the groups she examines in Russia, Norway and Finland, the cult means different things and stands for different ideals, especially when this issue is examined from national perspectives. However, if we zoom in to examine the context locally, the national "grand narratives" dissolve, enabling us to see the potential of a form of translocal memory that establishes a dialogue between local inhabitants and nature. Taking such an approach enables us to reach a new, ecological understanding of memory. Peer reviewed